Factors affecting deterioration of RC structures in waste water treatment plants - Gavino, Arlene A.; Marin, Marchal Anddrew dG.; Orozco, Christian R. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
RC structures present in waste water treatments plant are exposed to an aggressive environment where physical conditions, aggressive bacterial components and various kinds of chemical substances exist. These substances and microbes react with concrete through different mechanisms that lead to the corrosion of the reinforcement and eventually to the deterioration of concrete that could permanently damage the structure. The purpose of this study was to determine the factors affecting the deterioration of RC structures in waste water treatment plants. Base data were gathered from a compilation of 150 published journals related to concrete deterioration, after which a general factor mapping of the deterioration of RC structure was devised. The utilization of the general map and further study on waste water treatment schemes yielded three (3) treatment stage-specific maps focusing on the three main stages of SBR and MBBR treatment. The specific maps were then referenced in several case studies thru actual site inspection where actual modes of deterioration were observed and confirmed with both the general and the specific maps.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Buildings, Reinforced concrete; Reinforced concrete construction -- Corrosion; Sewage disposal plants -- Design and construction